Functions of Teacher and Student Code-Switching in an EFL Classroom and Pedagogical Focus: Observations and Implications - Stefan Rathert (ÜNİVERSİTEPARK Limited, 2012)
Code-switching (CS), the alternation between two or more languages within a stretch of language, is accepted as a valuable strategy of bilinguals in making linguistic choices for communicative purposes. Following different perspectives, CS can be understood either as an attempt to communicate meanings at the macro level (such as identity, solidarity etc.), or to convey intended meaning to the listener within the boundaries of conversational interaction at the micro level. Accepted as a strategy of speakers in bilingual communities, CS in foreign language learning settings is still a contentious matter. However, its potential has been emphasized in recent studies. This small-scale study examines teacher and student CS occurrences in an EFL lesson at a Turkish state university. CS occurrences were transcribed and sample extracts were analyzed through conversational analysis. The results show that teachers and learners apply CS to generate access to language or as a tool in classroom management. This study also reveals that CS can be a learner strategy to avoid L2 when lesson content is of little relevance to learners. In such cases CS cannot fulfil its potential as a means in discourse strategy, and language learning is unlikely to be facilitated.